2017
DOI: 10.1177/0300060517715375
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pulmonary function and functional capacity in adolescents with mild idiopathic scoliosis: observational cohort study

Abstract: ObjectiveThis observational cohort study aimed to evaluate ventilatory function (VF) and functional exercise capacity (FEC) in mild adolescent idiopathic scoliosis (AIS).MethodsSeventy-three adolescents with idiopathic scoliosis, aged approximately 10 to 17 years (mean age: 13.43 ± 1.27 years), with a Cobb angle less than 20° (mean: 16.44° ± 1.59°), met the inclusion criteria and were assigned to group A. Another 34 healthy adolescents with normal VF and FEC served as controls (group B). Forced vital capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 54 publications
2
37
0
2
Order By: Relevance
“…Redding The choice of a Cobb angle > 50° was based on surgical cut-offs. Since it is a common belief that there is no respiratory impairment at this degree of scoliosis, we showed that PFTs are modified early in the natural history of scoliosis, in accordance with Abdelaal et al, who reported from an observational cohort study that even adolescents with mild idiopathic scoliosis had mild pulmonary and functional restriction (24).…”
Section: Pulmonary Function and Spinal Parameterssupporting
confidence: 92%
“…Redding The choice of a Cobb angle > 50° was based on surgical cut-offs. Since it is a common belief that there is no respiratory impairment at this degree of scoliosis, we showed that PFTs are modified early in the natural history of scoliosis, in accordance with Abdelaal et al, who reported from an observational cohort study that even adolescents with mild idiopathic scoliosis had mild pulmonary and functional restriction (24).…”
Section: Pulmonary Function and Spinal Parameterssupporting
confidence: 92%
“…In AIS patients, prolonged relaxed sitting led to an even greater trunk asymmetry due to the habitual leaning on one side depending on the curvature type [ 10 ]. Knowing the health complications related to scoliosis (musculoskeletal, psychological and respiratory conditions) which seem to progress with an increase in the scoliosis curvature [ 11 14 ] it is important to identify PA and ST as important factors in assessing health status of patients with AIS.…”
Section: Introductionmentioning
confidence: 99%
“…(15) The present case suffered from right rib hump for two years associated with difficulty of breathing although his pulmonary function was normal thus supported by previous study that showed the spirometry and functional capacity restrictions are not correlated with the degree of spinal curvature in adolescents with mild AIS. (16) There are many studies showed that chest cage rigidityof thoracic scoliosis may contribute to pulmonary function deficits in scoliosis patients, increases with age, could in part account for the observation that respiratory failure can occur in adult IS patients even when there is no progression of the curvature. (15,16) Yet in recent years some spine surgeons have argued that, with the exception of cases diagnosed before the age of five years and with a Cobb angle of >100 degrees, IS patients suffer from 'no functional limitations' and that, moreover, the improvement of 'appearance and deformity with all its social and psychological deprivation is the only indication for treatment'.…”
Section: Discussion:-mentioning
confidence: 99%
“…(16) There are many studies showed that chest cage rigidityof thoracic scoliosis may contribute to pulmonary function deficits in scoliosis patients, increases with age, could in part account for the observation that respiratory failure can occur in adult IS patients even when there is no progression of the curvature. (15,16) Yet in recent years some spine surgeons have argued that, with the exception of cases diagnosed before the age of five years and with a Cobb angle of >100 degrees, IS patients suffer from 'no functional limitations' and that, moreover, the improvement of 'appearance and deformity with all its social and psychological deprivation is the only indication for treatment'. (15,17) In context of treatment,the goal of the treatment is a curve with a Cobb angle of <40° at skeletal maturity.…”
Section: Discussion:-mentioning
confidence: 99%